2018
DOI: 10.1002/jcla.22646
|View full text |Cite
|
Sign up to set email alerts
|

D‐dimer level in liver transplant recipients on the first day after surgery is correlated with postoperative thrombosis recurrence

Abstract: D-dimer level on the first day after liver transplant is related to thrombosis recurrence and is an independent risk factor for postoperative thrombosis recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…In an adult study, Zhang et al [4] reported that D-dimer level on the first day after liver transplant is related to thrombosis recurrence and is an independent risk factor for postoperative thrombosis recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an adult study, Zhang et al [4] reported that D-dimer level on the first day after liver transplant is related to thrombosis recurrence and is an independent risk factor for postoperative thrombosis recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported the relation of D-dimer to the occurrence of vascular thrombosis post-liver transplantation (LT) [4]. However, it is known that there are many changes in the hemostatic system in hepatic patients [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 We summarized the results from previous studies that investigated the cutoff DD and/or SFMC levels to detect VTE and the results of the present study (Table 4). [20][21][22][23][24][25][26] Clinical trials on anticoagulant therapy before the detection of VTE were excluded. Although there were several studies in the field of orthopedics, only three studies, which were conducted in patients who underwent surgery for portal hypertension or liver transplantation, 21,23,26 have been reported in the field of gastroenterological surgery.…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%
“…[20][21][22][23][24][25][26] Clinical trials on anticoagulant therapy before the detection of VTE were excluded. Although there were several studies in the field of orthopedics, only three studies, which were conducted in patients who underwent surgery for portal hypertension or liver transplantation, 21,23,26 have been reported in the field of gastroenterological surgery. In addition, no study has been conducted on the serum DD and/or SFMC level in patients who underwent HBP surgery.…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%